Desarrollo de un sistema SCADA para el abastecimineto de agua en la estación de bombeo Yuyucocha de la empresa municipal de agua potable y alcantarillado de Ibarra - Murillo Moreno, Darío Hernán (2018)
The present technical project was developed in the Municipal Drinking Water and Sewerage Company of Ibarra with the purpose of developing a SCADA system for the water supply system in the Yuyucocha pumping station, using fiber optic for the connection between three wells and the control room. The SCADA system of the Yuyucocha pumping station allows the continuous monitoring and control of the equipment that is used for the administration of drinking water in the city of Ibarra. Furthermore, through the HMI it allows observing the operating parameters and alarms that may occur in the process of the water pumping system in order to execute control actions against anomalies that may arise to solve the problem in a fast and timely manner. It was decided to monitor variables of level, flow, pressure, energy measurements, speed of the inverter and the control of ignition of pumps since the operators determine which data and main functions will help them to improve the service of distribution of potable water to the city of Ibarra. To establish communication between the different water wells located in different sectors of Yuyucocha, a fiber optic connection is made to be able to acquire data from all the wells to the SCADA system. The Schneider M340 Master PLC, located in the control room of the pumping station, acquires the information of all the variables to be controlled from the different wells connected to the optical fiber and is also programmed to generate communication failure alarms, problems in the drive, water levels, on and off status of water pumps.